E Efektivitas Pemberian Edukasi Dengan Metode Focus Group Discussion (FGD) Menggunakan Media Audio-Visual Terhadap Rasionalitas Penggunaan Antibiotik Di Desa Kresik Bura - Mursidah, Diana Aulia; Saputri, Rina; Aryzki, Saftia; Syamsu, Erlina (LPPM Universitas Sari Mulia, 2023)
Background: Irrational use of antibiotics can lead to therapy failure and the risk of resistance. One of the factors that influence the use of antibiotics is knowledge that can be increased by providing education. The FGD method aims to explore more specific issues related to the topics discussed. Education with audio-visual media facilitates the delivery of information and is more easily accepted by the public. Objective: To analyze the effectiveness of providing education using the Focus Group Discussion (FGD) method using audio-visual media on the rationality of using antibiotics in the people of Kresik Bura Village Method: True experimental with pretest posttest control group design. The sampling technique used was stratified random sampling with a total sample of 100 respondents. This research was conducted in Kersik Bura Village in June 2023-July 2023. Results: The results of the rationality of using antibiotics before education with a rational result of 40%, after being given education there was an increase to 72%. The results of the Wilcoxon test in the control group were 0.180 and in the experimental group 0.000. The results of the Mann-Whitney test obtained a p-value of 0.000. Conclusion: Providing education using the FGD method using audio-visual media is effective in increasing the rationality of using antibiotics.